PHONETIC ELEMENTS IN ENGLISH AND UZBEK LANGUAGES - Quttibayeva Balnur Asilbekovna; Bafoyeva Nilufar Salimovna (PEDAGOGS, 2024)
Annotation: This article examines the phonetic elements of English and Uzbek, highlighting both differences and similarities between the two languages. It provides a detailed comparison of their consonant and vowel inventories, noting the presence of unique sounds in each language. The article discusses stress and intonation patterns, showing how English has more complex and variable stress compared to the predictable stress patterns in Uzbek. It also covers phonotactics, indicating that English allows more complex consonant clusters than Uzbek. Additionally, the article explores phonological processes like assimilation and elision, demonstrating their occurrence in both languages albeit with different frequencies and contexts. Overall, this comparison underscores the distinct phonetic characteristics rooted in the linguistic heritages of English and Uzbek, while also recognizing shared phonetic processes